Tracking anthropological engagements - Darnell, Regna; Gleach, Frederic W. (Frederic Wright), 1960- (Histories of anthropology annual, 2018)
"Histories of Anthropology Annual series presents diverse perspectives on the discipline's history within a global context, with a goal of increasing awareness and use of historical approaches in teaching, learning, and conducting anthropology. The series includes critical, comparative, analytical, and narrative studies involving all aspects and subfields of anthropology. Volume 12, Tracking Anthropological Engagements, examines the work and influence of Hans Sidonius Becker, Franz Boas, Sigmund Freud, Margaret Mead, Karl Popper, and Anthony F.C. Wallace, as well as anthropological perspectives on the 1964 Project Camelot, Latin American cultures at the 1892 Madrid International Expositions, sixteenth-century cosmography and topography in Amazonia, the launch of the Great War Centenary Association website, and community-produced wartime narratives in Ontario, Canada."--